Discourse versus action in school management and curriculum practices: an investigative overview during reform times. (Praxis Educativa, 2012)
In this article we critically discuss issues about school management and curriculum practices during reform times and how these should be subjected to research. We describe the political and curricular information that explains the Educational Reform in Chile. We also analyze theoretical terms that underlie concepts such as structure, organization, curriculum, and from there we start to reflectively discuss issues about the discourse and actual performance of educators and head administrators in times of reform. Lastly, we propose to develop research projects that illustrate the complexity of the relationships established within educational institutions, so as to implement practices of school and curriculum management that assure freedom of expression among the members of the school system. Thus, everyone has the opportunity of playing different roles in this debate based on the acknowledgement of the other as a rightful interlocutor in this process of joint construction.
Keywords: management; curriculum; Chilean reform; discourse and action; actors' protagonism